Factors that Make Up the Process of “Desgaleguización” of the Galician Inmigrants in Buenos Aires - Soto Andión, Xosé (Madrygal. Revista de Estudios Gallegos, 2004)
In this paper we look at the diverse factors that make up the process of desgaleguización of Galician immigrants in Buenos Aires. From this point the following questions are addressed: the situation in society and the linguistic conflict in the Galicia the emigrants had abandoned, the phenomena of migration as such, the feeling of identification with the country and the language of origin. The social-work status of the immigrant, the distancing and adaptation to the new environment, the contact and interference between two languages in the diaspora. Emigrant, country of origin, hosting country, lenguage, identity, conflict.